Insurers’ responses to cyber crime: evidence from Russia - Timofeyev, Yuriy (International journal of law, crime and justice, 2022)
This study aims to identify effective responses to cyber crime in the insurance industry. Survey responses from Moscow-based employees holding key positions in the leading insurance companies have been collected. The study analyses awareness of, attitudes to, and approaches to cyber security, as well as the incidence and impact of breaches or attacks. According to the experts, complying with laws or regulations and preventing fraud or theft are the main reasons for investing in cyber security. Phishing, viruses, and unauthorised use of computers, networks or servers by staff are the most widely spread threats to cyber security. Russian insurers often undertake additional staff training or change their policies in response to cyber breaches. Strategic recommendations were elaborated for industry professionals.